Organizational commitment and intention to leave among nurses in Malaysian public hospitals - Omar, Khatijah; Mohamed Anuar, Marhana; Abdul Majid, Abdul Halim; Johari, Husna (Centre for Promoting Ideas, 2012)
The study investigates the relationship between organizational commitment and intention to leave among nurses in Malaysian public hospitals and it focuses on public hospital nurses in Peninsular Malaysia.Results of analysis confirmed that organizational commitment was significantly and negatively related to intention to leave and the results were a crucial consideration enabling management and employers attain ample understanding and guidelines if they were to draft retention strategies.Even though many studies had been conducted on intention to leave, most of them were conducted in developed countries.Thus, this study is believed to enhance the literature gap since it has an emphasis on the Malaysian context.